Murder at an Irish chipper - O'Connor, Carlene (O'Connor, Carlene. Irish village mystery., 2025)
"Taking a holiday by the sea to eat enough fish and chips to support the struggling business of the aptly named Mrs. Chipper, newlyweds Siobhan and Macdara Flannery instead find the proprietor murdered and place their long-delayed honeymoon on hold to catch a slippery killer"--